Cultural differences in stigma surrounding schizophrenia: Comparison between Central Europe and North Africa. (April 2016) - Angermeyer, Matthias C.; Carta, Mauro G.; Matschinger, Herbert; Millier, Aurélie; Refaï, Tarek; Schomerus, Georg; Toumi, Mondher
Abstract : Background: Exploring cultural differences may improve understanding about the social processes underlying the stigmatisation of people with mental illness. Aims: To compare public beliefs and attitudes about schizophrenia in Central Europe and North Africa. Method: Representative national population surveys conducted in Germany (2011) and in Tunisia (2012), using the same interview mode (face to face) and the same fully structured interview. Results: In Tunisia, respondents showed a stronger tendency to hold the person with schizophrenia responsible for the condition. At the same time they expressed more prosocial reactions and less fear than their German counterparts. In Germany, the desire for social distance was greater for more distant relationships, whereas in Tunisia this was the case for close, family-related relationships. Conclusions: Stigma differs between Tunisia and Germany more in form than in magnitude. It manifests particularly in those social roles which 'matter most' to people within a given culture.